Україна й інформаційна демократія: новий вимір політики - Митко, Антоніна (Видавництво Львівської політехніки, 2014)
Розглянуто новітнє для України явище – інформаційну демократію як новий вимір ведення політики. Проаналізовано як інформаційна демократія впливатиме на процеси та прийняття рішень у політичній сфері. Охарактеризовано проблеми, з якими стикається наша держава під час входження в інформаційне суспільство. Досліджено позитивні та негативні наслідки для країни під час входження у глобалізований інформаційний простір. The purpose of the article to analyze how the information influences the processes of democracy and decision-making in the political sphere. The problems which are faced by Ukraine from the entry into the globalized information environment are described. The article is about the newest phenomenon in Ukraine – information democracy, as a new dimension of politics. It is analyzed how information democracy will affect the processes and decisionmaking in the political sphere. The challenges facing our state, from entry into the information society are described. The positive and negative consequences for the country when entering the globalized information space are studied. It is proved that the main issues that need immediate resolution of the position information of democracy are necessary to include open partnership of government, law enforcement agencies, businesses, civic and international organizations in the development of information and communication technologies, the introduction of e-governance and self-development of e-commerce, cybercrime, the protection of freedom of expression and media pluralism, good management of critical Internet resources, the preservation of cultural diversity, the development of e-learning, e-health, e-environment protection. It will ensure transparency, accountability and responsibility in decision-making in the development of information democracy in Ukraine. The investigation of the formation and development of democracy in Ukraine information is fragmented, holistic research with a focus on some positive and negative aspects of it.
Ukraine and information democracy: a new dimension of politics
Keywords: інформаційна демократія; інформаційне суспільство; політика; система; information democracy; information society; politics; system; positive and negative aspects